2013
DOI: 10.1371/journal.pone.0063067
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Ligase Praja1 Reduces NRAGE Expression and Inhibits Neuronal Differentiation of PC12 Cells

Abstract: Evidence suggests that regulated ubiquitination of proteins plays a critical role in the development and plasticity of the central nervous system. We have previously identified the ubiquitin ligase Praja1 as a gene product induced during fear memory consolidation. However, the neuronal function of this enzyme still needs to be clarified. Here, we investigate its involvement in the nerve growth factor (NGF)-induced differentiation of rat pheochromocytoma (PC12) cells. Praja1 co-localizes with cytoskeleton compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Notably, Mage-d1-null mice display decreased extracellular serotonin levels and increased serotonin transporter (SERT) protein levels, suggesting that deficiency in MAGE-D1 induces both behavioral and neurological phenotypes of depression [81]. Further investigation revealed that MAGE-D1 regulates ubiquitination and proteasomal degradation of SERT, consistent with previous reports associating MAGE-D1 with PRAJA-1 E3 ligase and modulation of Msx2- and Dlx5-dependent transcription as well as neuronal differentiation [8183]. In an alternative Mage-d1-deficient (hemizygous) mouse model, loss of Mage-d1 results in reduced social interactions, decreased sexual activity leading to infertility in males, reduced motor activity, late-onset obesity associated with hyperphagia, and increased anxiety-like behaviors [84].…”
Section: Physiological Expression and Functionsupporting
confidence: 81%
“…Notably, Mage-d1-null mice display decreased extracellular serotonin levels and increased serotonin transporter (SERT) protein levels, suggesting that deficiency in MAGE-D1 induces both behavioral and neurological phenotypes of depression [81]. Further investigation revealed that MAGE-D1 regulates ubiquitination and proteasomal degradation of SERT, consistent with previous reports associating MAGE-D1 with PRAJA-1 E3 ligase and modulation of Msx2- and Dlx5-dependent transcription as well as neuronal differentiation [8183]. In an alternative Mage-d1-deficient (hemizygous) mouse model, loss of Mage-d1 results in reduced social interactions, decreased sexual activity leading to infertility in males, reduced motor activity, late-onset obesity associated with hyperphagia, and increased anxiety-like behaviors [84].…”
Section: Physiological Expression and Functionsupporting
confidence: 81%
“…1B and C ), suggesting that PJA1 acts as a potential antiviral factor against HBV. PJA1 encodes two isoforms, PJA1 and PJA1B, with a 55-amino-acid difference ( 6 ), and the N-terminus-lacking isoform, PJA1B, was reported to function consistently with full-length PJA1 in nerve growth factor-induced differentiation of rat pheochromocytoma cells ( 50 ). Here, we generated four plasmids expressing PJA1; PJA1B; PJA1ΔR, which lacks the RING domain; and PJA1BΔR, which lacks the RING domain ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The latter interactions may represent different interaction types. For example, MAGED1-Praja1 interaction, which directs MAGED1 to proteasomedependent degradation, 31,48 represents a substrate-ligase type of interaction rather than the stimulation-of-ligase type of interaction proposed for MAGEA1-TRIM31. In other words, different MAGE-RING interactions may have different natures, may serve different purposes and may have different evolutionary origins.…”
Section: Discussionmentioning
confidence: 99%